The efficacy of intravitreal bevacizumab for acute central serous chorioretinopathy - Aydin, Erdinc (Journal of ocular pharmacology and therapeutics, 2013)
To investigate the efficacy of intravitreal bevacizumab injection in patients with acute central serous chorioretinopathy (CSCR). Between 6 weeks and 3 months, 13 eyes of 22 patients with acute CSCR received an intravitreal bevacizumab injection (2 mg/0.08 mL), 9 eyes had no medical treatment as a control. At baseline and follow-up visits patients had best corrected visual acuity (BCVA), intraocular pressure assessment, dilated fundus examination, and spectral optical coherence tomography imaging. Outcome measures were the resolution of neurosensory detachment, improvement in visual acuity, and symptoms. All patients showed prompt improvements of visual acuity and symptoms until the 3rd month and recovered from neurosensory detachment gradually following treatment in the study group. The vision of control subjects recovered later and the regression of serous retinal detachments were fairly slow. The mean BCVA improved from 0.39±0.16 at first visit (at baseline) to 0.73±0.17 at the 6th month in the study group; and, from 0.25±0.17 at first visit (at baseline) to 0.67±0.13 at the 6th month in the control group that was statistically significant (P=0.0001; P=0.0001, respectively). Mean retinal thickness for the study group was decreased from 414.38±102.79 at first visit (at baseline) to 256.46±84.77 at the 3rd month and 198.30±29.81 at the 6th month (P=0.0001, P=0.0001); and that for the control group was decreased from 510.33±80.59 at first visit (at baseline) to 336.33±127.83 at the 3rd month and 205.66±19.65 at the 6th month (P=0.004, P=0.0001, respectively). One of the patients in the control group revealed recurrence at the 6th month and the patient was given intravitreal injection of bevacizumab. Intravitreal bevacizumab injection for acute CSCR can lead to remarkable improvements of visual acuity within 3 months follow-up compared with controls. These results demonstrated that intravitreal bevacizumab injection may be a promising option for selected patients in the treatment of acute CSCR.